Spatial Distribution and Accessibility Analysis of Mosques in Bogor City Using GIS-Based Buffer Zone Analysis - Rina Trisminingsih; Muhammad Faiz (Program Studi Sistem Informasi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Raden Fatah Palembang, 2026)
Mosque development in rapidly urbanizing areas is often driven by local initiatives, creating potential disparities in spatial distribution and accessibility. This study aims to develop a WebGIS-based framework to analyze the spatial distribution of mosques and assess their potential service coverage in Bogor City, Indonesia. A total of 785 mosque records from Sistem Informasi Masjid were integrated with district-level population data and administrative boundaries. Variable-radius buffers were generated from population density and mosque congregation capacity, while the WebGIS platform supported interactive filtering, visualization, and spatial exploration. The analysis revealed contrasting patterns: selected locations in Bogor Selatan exhibited greater buffer overlap and a relatively concentrated arrangement, whereas Bogor Barat showed a more dispersed pattern. Preliminary verification classified seven of ten georeferenced records as appropriate. However, because mosque locations were generated through city-name georeferencing rather than verified coordinates, the findings should be interpreted as exploratory. The proposed framework therefore serves as a preliminary tool for visualizing mosque distribution and potential service coverage at the city level.